Dataset for the study of the effect of anticoagulation in the incidence of stroke and other outcomes in patients with left ventricular thrombus - Álvaro Lorente-Ros; Marta Lorente-Ros; Gonzalo L. Alonso-Salinas; Juan M. Monteagudo Ruiz; Covadonga Fernández Golfín; José L. Zamorano Gómez (Data in Brief, 2023)
The optimal duration of anticoagulation in patients with left ventricular thrombus (LVT) is unknown. The data package herein presented contains the information used to assess the effect of duration of anticoagulation in the incidence of stroke in patients with left ventricular thrombus (LVT) in a tertiary hospital. In order to collect the required data, all transthoracic echocardiography studies at our institution from January 1st 2014 to December 31st 2021 with LVT were retrieved using dedicated software (Phillips Intellispace Cardiovascular; Koninklijke Phillips N.V., 2004-2020). Second, a dataset was designed ad hoc for this study in which the recruited data for the predefined objectives were obtained from electronic medical records. These data included clinical and demographic information including treatment choices (vitamin K antagonists [VKA] versus direct oral anticoagulants [DOAC]), duration of treatment, reason for interruption of treatment, occurrence of stroke, acute myocardial infarction, bleeding events, thrombus resolution, recurrence, and death. Retrieved data were stored in an excel sheet for analysis using the statistical package STATA (StataCorp v. 15.0, College station, TX). This methodology allows the reuse of these data for further analysis, in the context of the present study and also for future recruitment of additional patients from other institutions to increase statistical power.